Reviev paperHormonal factors in aetiology and therapy of acne vulgaris - Sobjanek, Michał; Sokołowska-Wojdyło, Małgorzata; Barańska-Rybak, Wioletta; Nowicki, Roman; Włodarkiewicz, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Acne vulgaris is a chronic disorder connected with hyper-secretion of sebaceous glands affecting people between 12 and 40 years old. It is one of the most common dermatological problems. Treatment is a long process in which good cooperation between patient and doctor is necessary. Hormonal factors, essentially androgens, sex and growth hormones and melanocortin, play an important role in the pathogenesis of acne. Precise mechanisms which regulate normal function of sebaceous glands are still unclear. The use of contraceptives among other forms of treatment in acne vulgaris is common. Spironolacton and flutamid can be used as elements of combined therapy. We present a review of the role of hormonal factors in the pathogenesis and therapy of acne.